2000
DOI: 10.1093/ndt/15.3.396
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of residual renal function to overall nutritional status in chronic haemodialysis patients

Abstract: Over half of our HD patients had sufficient RRF. RRF itself may have a beneficial effect on nutritional parameters, and it is important to determine RRF over time, even in chronic HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
87
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 23 publications
9
87
0
Order By: Relevance
“…35 RRF also contributes to overall nutritional status in maintenance hemodialysis patients. 36 Hemodialysis patients with stable urine output have a greater lean body mass, an indicator of nutritional status in maintenance hemodialysis patients, than do those without RRF, 36 a finding that is consistent with our findings. Loss of RRF has been associated with an increased inflammatory response 37 and may enhance an inflammatory response via increased oxidative stress, a situation that may lead to activation of monocytes and production of cytokines.…”
Section: Discussionsupporting
confidence: 90%
“…35 RRF also contributes to overall nutritional status in maintenance hemodialysis patients. 36 Hemodialysis patients with stable urine output have a greater lean body mass, an indicator of nutritional status in maintenance hemodialysis patients, than do those without RRF, 36 a finding that is consistent with our findings. Loss of RRF has been associated with an increased inflammatory response 37 and may enhance an inflammatory response via increased oxidative stress, a situation that may lead to activation of monocytes and production of cytokines.…”
Section: Discussionsupporting
confidence: 90%
“…Detection of creatinine and urea clearance is a heavy burden for chronic dialysis patients because it requires collection of urine for 24 h. Therefore, some studies used the dialysis between 24 h urine to evaluate RRF. 1,21,22 Moist et al 22 showed that the urine of hemodialysis patients was positively correlated with the inulin clearance rate (correlation coefficient: 0.71) and the correlation coefficient of urine for 24 h with the mean of creatinine and urea clearance was 0.57 (p ¼ 0.001). Van Olden et al 23 also observed a significant positive correlation between GFR and urine volume for 24 h. These results support that 24 h urine volume is an effective indicator for the evaluation of RRF.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also used this indicator to define RRF loss (24 h urine < 200 mL). 21,22 Under the hemodialysis condition, it is required to clear 60-70 L plasma water weekly in order to ensure the removal of the body's toxin. Studies have shown that the RRF is 1 mL/min, which is equivalent to the weekly removal of approximately 10 L of plasma water.…”
Section: Discussionmentioning
confidence: 99%
“…The residual renal function is probably an important predictor of outcome in HD patients as well (14,15). However, the relative contribution of residual renal Kt/V urea (rKt/V urea ) versus delivered Kt/V urea (dKt/V urea ) to patient outcome remains to be established for HD patients.…”
mentioning
confidence: 99%